1999
DOI: 10.2308/acch.1999.13.3.241
|View full text |Cite
|
Sign up to set email alerts
|

Corporate Reporting on the Internet

Abstract: In this paper, we examine firms' use of the Internet to enhance the relevance of their financial reporting. We define a firm as practicing Internet Financial Reporting (IFR) when it provides in its web site either (1) a comprehensive set of financial statements (including footnotes and the auditors' report), (2) a link to its annual report elsewhere on the Internet or (3) a link to the U.S. Security and Exchange Commission's (SEC) Electronic Data Gathering, Analysis and Retrieval (EDGAR) system. While 70 perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
373
8
49

Year Published

1999
1999
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 424 publications
(453 citation statements)
references
References 2 publications
23
373
8
49
Order By: Relevance
“…For example, studies have examined IFR in countries including the US (see, e.g., Ashbaugh et al, 1999;Ettredge et al, 2001;Patten, 2002b), Germany (see, e.g., Marston and Polei, 2004), Spain (see, e.g., Gowthorpe and Amat, 1999), and Sweden (see, e.g., Hedlin, 1999), as well as in companies across different countries (see, e.g., Flynn and Gowthorpe, 1997;Debreceny et al, 2002).…”
Section: Background and Prior Researchmentioning
confidence: 99%
“…For example, studies have examined IFR in countries including the US (see, e.g., Ashbaugh et al, 1999;Ettredge et al, 2001;Patten, 2002b), Germany (see, e.g., Marston and Polei, 2004), Spain (see, e.g., Gowthorpe and Amat, 1999), and Sweden (see, e.g., Hedlin, 1999), as well as in companies across different countries (see, e.g., Flynn and Gowthorpe, 1997;Debreceny et al, 2002).…”
Section: Background and Prior Researchmentioning
confidence: 99%
“…Several national and international studies have documented increases in the number of companies reporting corporate information via the Internet, and have reported increases in the volume of information disclosed via this medium (see Lymer et al (1999), Trites (1999), Deller et al (1999, Ashbaugh et al (1999Ashbaugh et al ( ), F.A.S.B. (2000, Geerings et al, (2003)).…”
Section: The Impact Of the Internet On Investor Relationsmentioning
confidence: 99%
“…A survey by Ashbaugh et al (1999) found that those firms engaged in online corporate reporting placed greater emphasis on communications with potential and existing shareholders. Interviews conducted by Ettredge et al (2001) found that IR directors do see the Web site as a means of reducing administrative costs and that online disclosure helps provide a common level of disclosure to all stakeholders.…”
Section: Other Motivations For Investor Relations Websitesmentioning
confidence: 99%
See 1 more Smart Citation
“…Response rates obtained for preparers/finance directors in the UK have been: 18% (Bebbington et al, 1994); 6% and 35% (Nixon, 1997); 32% (Arnold and Hatzopoulos, 2000); 30% (Manson and Zaman, 2001). Studies in other countries report the following: US: 12% (Trahan and Gitman, 1995); 27% (Ashbaugh et al, 1999); 9% (Graham and Harvey, 2001); Australia: 25% (Deegan and Rankin, 1999); New Zealand: 25% (Milne and Chan, 1999). Illustrative response rates for expert users/investment analysts have been UK: 22% (Solomon, 1999); 20% (Clatworthy, 2000); 23% (Manson and Zaman, 2001); Australia: 35% (Yap, 1997); 25% (Deegan and Rankin, 1999); New Zealand: 21% (Milne and Chan, 1999).…”
Section: Notesmentioning
confidence: 99%